Laparoscopic Assessment to Determine the Likelihood of Achieving Optimal Cytoreduction in Patients Undergoing Primary Debulking Surgery for Ovarian, Fallopian Tube, or Primary Peritoneal Cancer. (October 2018) - Andikyan, Vaagn; Kim, Annie; Gretz, Herbert F.; Zakashansky, Konstantin; Prasad-Hayes, Monica; Beddoe, Ann-Marie; Dottino, Peter; Mandeli, John; Chuang, Linus
Abstract : Objective: The objective of this study was to evaluate the safety and efficacy of laparoscopic assessment to determine the likelihood of achieving optimal cytoreduction (OC) in patients undergoing primary debulking surgery (PDS) for ovarian cancer. Methods: All patients who underwent diagnostic laparoscopy and PDS at our institution from January 2008 to December 2013 were identified. We determined the likelihood of achieving optimal cytoreduction by laparoscopic assessment based on tumor site, pattern of spread, and disease burden. Sensitivity was defined as the number of patients who achieved optimal cytoreduction after laparoscopic assessment divided by the number of patients with disease deemed resectable by laparoscopy. Results: We identified 55 patients during study period. Twenty-one of the 55 patients (38%) were early stage disease. Six (10.9%) patients had disease deemed unresectable and 49 (89.1%) had disease deemed resectable at the time of laparoscopy. OC was achieved in 48 of 49 (97.9%) patients. The sensitivity of laparoscopy in predicting OC was 98% (95% confidence interval, 89.3%-99.9%). The operation was completed laparoscopically in 23 of 49 patients (47%); in 26 of 49 (53%), PDS was performed by laparotomy. There were no port site metastases reported. The rate of postoperative complications was 16%. With a median follow-up of 30 months, the median overall survival was not reached and the 75th percentile for overall survival was 37 months. Conclusions: Laparoscopy was shown to have a high sensitivity in predicting OC and is a feasible tool in triaging patients with ovarian cancer. Laparoscopy is not associated with adverse surgical outcomes.